A Review on Bilayer Tablet Technology for Multi Modal Drug Delivery - Jangid, Vikash; Chatterjee, Dr. Arindam; Agrawal, Dr. Vikash; Kumar Gupta, Manoj; Garg, Pradeep (Journal of Biomedical and Pharmaceutical Research, 2022)
Bilayer tablets are cutting-edge drug delivery technologies that enable the delivery of two medicines with various release patterns combined in a single unit. Bilayer tablets can deliver two incompatible medications in a single formulation, prolong the effect of the drug(s), and increase patient compliance. Bilayer tablets feature an active substance in one layer that is released immediately and another layer that is released later, either as a second dosage or in a prolonged release manner. The drawbacks of single-layered tablets are being overcome by the advancement of useful technology in bilayer tablets. Bilayer tablet technology requires a lot of resources, though. For each technical stage, a careful selection of excipients and manufacturing conditions is also necessary. High blood pressure patients frequently struggle or fail to control their BP with a single medication. To achieve treatment objectives, the majority of hypertension patients will require the use of two or more antihypertensive medications. When treating hypertension in patients whose blood pressure cannot be well controlled with monotherapy, combinations of antihypertensive medications from different categories have been demonstrated to be more successful than either medication alone. Combining two antihypertensive drugs with complementary modes of action may decrease blood pressure more effectively than using any one of these drugs by alone.Keywords: Bi-layer tablet, Tablet manufacturing, Bi-layer tableting techniques.